Impact of International North-South Transport Corridor (INSTC) on Indian Economy - Babu , P. Venkaiah; Agarwal , C. S. Monika; Seethamahalakshmi , M. (Recent Advances in Commerce, Management, and Tourism, 2023)
The International North-South Transport Corridor (INSTC) is a multi-modal transportation system that connects India, Russia, and Europe through a network of shipping, rail, and road routes. The INSTC aims to reduce the transit time and costs of transporting goods between these regions, and to increase connectivity and trade. In this study, we investigate the impact of the INSTC on international trade between India, Russia, and Europe. We analyzed trade data from the past decade to evaluate changes in the volume and value of trade between these regions before and after the establishment of the INSTC. Additionally, We have also surveyed the business community involved in the trade of these regions to get an insight on their experience with the INSTC and its impact on their trade activities. Our findings indicate that the INSTC has significantly reduced the transit time and costs of transporting goods between these regions, resulting in an increase in the volume and value of trade. Furthermore, the survey results show that the majority of the business community is satisfied with the INSTC and it has helped them to increase their trade activities. Overall, this study provides evidence that the INSTC has had a positive impact on international trade between India, Russia, and Europe, and has helped to promote economic growth and development in the region.